If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3G + -9 = -24 Reorder the terms: -9 + -3G = -24 Solving -9 + -3G = -24 Solving for variable 'G'. Move all terms containing G to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -3G = -24 + 9 Combine like terms: -9 + 9 = 0 0 + -3G = -24 + 9 -3G = -24 + 9 Combine like terms: -24 + 9 = -15 -3G = -15 Divide each side by '-3'. G = 5 Simplifying G = 5
| 8x+9y=150 | | 6-12n=2 | | [4x+6]+[7x+15]=120 | | 3v=64-5v | | 2.3+5x=3x-5.7 | | 7(x-2)=3+3x | | 19=x-7 | | 14=3/2x-7 | | x/456=4 | | x/4456=4 | | 2x-14=2(2x+3) | | 9x-7=23x-14 | | x-2.6=7.3 | | 27=46+2x-1x | | 1.5m=0.5 | | -6x-21+9x=42 | | 2x+6=-7x-9 | | 27-(x+9)=4x-2 | | 6x-(2x+4)-(x+3)= | | 7(2y+1)=2(y-13) | | 0.4=0.75+y | | -6b+5(1-b)=-8b+26 | | (2x-1)(x^2-3x+5)=0 | | 3(2x+1)+1+2x=3(2x+2)+x | | 2X^2-16X+64= | | 7y-9-4y+4=0 | | 1.2x=40.8 | | 0(2x-4)^-11/2 | | -5+x-9=15 | | -1/4a7/4a=-21 | | 3/5x-3=2.25 | | 0.4=0.75y |